Citadela Nova project - archaeological research in 2024 (In situ, 2025)
In 2024, another archaeological investigation was conducted within the complex of the old Technical School building, in the part of the former school workshops. These investigations, by excavating at three positions, confirmed the assumption about the direction of the Nani-Dolfin connecting rampart. The investigation was conducted in order to better prepare the investor for planning the execution of construction works as part of the Citadel Nova project - reconstruction and extension of the workshop part of the old Technical School.
Keywords: Zadar; ramparts; Nani-Dolfin